APOPTOSIS INDUCTION EFFECT OF CURCUMIN AND ITS ANALOGS PENTAGAMAVUNON-0 AND PENTAGAMAVUNON-1 ON CANCER CELL LINES - Da’i, Muhammad; Suhendi, Andi; Meiyanto, Edi; A JENIE, UMAR; Kawaichi, Masashi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: This experiment aims to investigate the apoptosis effect of curcumin and its analogs pentagamavunon-0 (PGV-0) and PGV-1 on normal and other cancer cell lines. Methods: Growth inhibition effect was investigated using the MTT method. Double staining used acridine orange, 2-(4-aminodiphenyl)-6- indolcarbamidine dihydrochloride and ethidium bromide was performed to determine morphological changes of cells. Detection of PARP, caspase-3, PUMA and BAX using a western blot method was conducted to elucidate the apoptosis effect of the compounds. Results: PGV-1 (2.5 Î¼M) and PGV-0 (5.0 Î¼M) could inhibit T47D-cell growth on 72 h observation, but not for curcumin. DNA staining showed PGV-1 has the strongest apoptosis induction effect on T47D-cells compared to PGV-0 and curcumin as well. Western blot analysis resulted in cleavage PARP (83 kD) on HeLa, T47D, and MCF-7 cells treated with PGV-1 (2.5 Î¼M), PGV-0 (5.0 Î¼M). Curcumin (10.0 Î¼M) just induced apoptosis on T47D-cell and MCF-7 cell, but not HeLa cell. Cleavage PARP resulted by apoptosis process in the cell. PGV-1 (2.5 Î¼M) had a stronger apoptosis effect compared to PGV-0 (5.0 Î¼M) and curcumin (10.0 Î¼M) based on cleaved PARP result qualitatively. On the normal cell (NH3T3), cells that were treated with the compounds resulted in a negative cleavage PARP. This result indicated that the compounds were part of a selectively induced cancer cell line apoptosis process. Conclusion: Curcumin, PGV-0 and PGV-1 could inhibit cell growth by induce apoptosis on cancer cells but not on normal cells, which PGV-1 has strongest apoptosis induction effect on cancer cell lines. Keywords: Curcumin and analogs, Apoptosis, Cancer cell lines.